Neither the Cohabitation of the Father nor the Grandmother Can Help Exclusive Breastfeeding in Indonesia: Empirical Research Using SUSENAS 2019 and 2020 (Jurnal Perencanaan Pembangunan: The Indonesian Journal of Development Planning, 2022)
Exclusive breastfeeding (EBF) for the first six months is the key to preventing malnutrition in children. However, EBF coverage in Indonesia is only 38%, while the target WHO set in 2030 is 70%. Therefore, targeting the actors behind EBF completeness is needed to boost the EBF rate. The research will uncover the impact of the daily sources of support (both maternal and paternal grandmothers, the father, and the domestic worker) and modifying factors on the EBF choices made by the mother. Using the 2019 and 2020 National Socio-Economic Survey (SUSENAS) data, probit regression suggests that no one's cohabitation with the mother significantly affects EBF completeness. In contrast, maternal characteristics (employment status, economic level, education completion, and residential area of living), baby’s gender, and father’s education become the most decisive factors. Since the leading actor is still the mother herself, to improve the EBF rate, the policy should be focused on helping breastfeeding mothers to face the challenges, especially in the workplace.